Sonographic Appearance of Abdominal Wall at the Left Flank of Laparotomy Incision Site in Ettawah Grade Does - Mokhamad Fakhrul Ulum; Dedi R. Setiadi; Budianto Panjaitan; Muchidin Noordin; . Amrozi (Media Peternakan, 2014)
The aim of this study was to describe the sonographic appearance of abdominal wall at the left flank of laparotomy incision site in 11 mated Ettawah grade does. Brightness-mode ultrasound examination by using transducer with frequency of 5.0-6.0 MHz was conducted to grouping the does based on their pregnancy statuses. The incision site of the abdominal wall at left flank laparotomy was transcutaneous-scanned as long as 8 cm vertically. The sonographic appearance of the laparotomy wall thickness showed that in all groups of does were similar and not different statistically. The thickness of oblique external and oblique internal abdominal muscles increased in the pregnant does as compared to non-pregnant does (P<0.05).Key words: laparotomy, left flank, ultrasonography, incision site, Ettawah grade does